Combined Immunotherapy With Belatacept and BTLA Overexpression Attenuates Acute Rejection Following Kidney Transplantation - Zhang, Hengcheng; Wang, Zijie; Zhang, Jiayi; Gui, Zeping; Han, Zhijian; Tao, Jun; Chen, Hao; Sun, Li; Fei, Shuang; Yang, Haiwei; Tan, Ruoyun; Chandraker, Anil; et al. (Frontiers in Immunology, 2021)
Background: Costimulatory blockade provides new therapeutic opportunities for ensuring the long-term survival of kidney grafts. The adoption of the novel immunosuppressant Belatacept has been limited, partly due to concerns regarding higher rates and grades of acute rejection in clinical trials. In this study, we hypothesized that a combined therapy, Belatacept combined with BTLA overexpression, may effectively attenuate acute rejection after kidney transplantation. Materials and methods: The rat kidney transplantation model was used to investigate graft rejection in single and combined therapy. Graft function was analyzed by detecting serum creatinine. Pathological staining was used to observe histological changes in grafts. The expression of T cells was observed by immunohistochemistry and flow cytometry. In vitro, we constructed an antigen-stimulated immune response by mixed lymphocyte culture, treated with or without Belatacept and BTLA-overexpression adenovirus, to observe the proliferation of receptor cells and the expression of cytokines. In addition, western blot and qRT-PCR analyses were performed to evaluate the expression of CTLA-4 and BTLA at various time points during the immune response. Results: In rat models, combined therapy reduced the serum creatinine levels and prolonged graft survival compared to single therapy and control groups. Mixed acute rejection was shown in the allogeneic group and inhibited by combination treatment. Belatacept reduced the production of DSA and the deposition of C4d in grafts. Belatacept combined with BTLA overexpression downregulated the secretion of IL-2 and IFN-γ, as well as increasing IL-4 and IL-10 expression. We also found that Belatacept combined with BTLA overexpression inhibited the proliferation of spleen lymphocytes. The duration of the elevated expression levels of CTLA-4 and BTLA differentially affected the immune response. Conclusion: Belatacept combined with BTLA overexpression attenuated acute rejection after kidney transplantation and prolonged kidney graft survival, which suggests a new approach for the optimization of early immunosuppression after kidney transplantation.